THE PERFORMANCE OF TRADITIONAL CONTRACT PROCUREMENT ON HOUSING PROJECTS IN NIGERIA - Stephen O. Ojo; Olabosipo I Fagbenle; Aderemi Y Adeyemi (Institute of Research and Community Outreach - Petra Christian University, 2006)
The traditional contract procurement has been widely criticized as an ineffective procurement method because it often involves time and cost overrun on construction projects. Yet the method is still being widely used in Nigeria most especially for the procurement of housing projects. It is suspected that this procurement method may not be ineffective in all cost categories of housing projects. Therefore time and cost performances of the procurement method on 57 housing projects of varying cost categories initiated by the Nigerian government between 1993 and 1999 were studied. The category of one to five million naira (US1.00 â 92 Nigerian Naira in 1999) showed the least time overrun of 18.98% while the highest time overrun of 99.64 % was shown in the five to ten million naira. The over ten million naira category had the least cost overrun of 9.13% while the highest cost overrun of 34.55 % was shown in the less than one million naira. The one to five million naira cost category exhibited weak correlation between time and cost overruns but the five million naira and above categories showed strong correlation. It was concluded that one to five million naira cost category is quite suitable for traditional contract procurement on housing projects in Nigeria.